Collecting system and payroll tax compliance: Evidence from Chinese firm-level data - Jue Tang; Jin Feng (China Economic Quarterly International, 2021)
This paper quantifies the impacts of collecting system on social insurance contribution compliance, taking advantage of a reform around 2000 in China. Using firm-level data, we find that the actual contribution rate and the probability of participation were raised by 3% and 5 percentage points respectively, after changing the collection department from social security department to local tax department. Mechanism analyses show that the effect is larger in areas where the tax collection capacity is stronger and the reform had no significant effects on SOEs.